The semantic peculiarities of the terminology nomination (Eurasian Journal of Philology Science and Education, 2016)
The semantic peculiarities of the terminology nomination in the sphereof medical(anatomical) terminology on the example of double word andmultiword terms are solved in the article. It is noted, that metaphoricnomination is presented as a stable mechanism of replenishment of theresearched terminosystem. Special attention is paid to the consideration ofthe basic sources of the terminometaphors formation.Due to the observation it was established, that the anatomical terminologyis characterized by the wide usage of whole series of the metaphoricmodels. More typical models were presented, confirming the systematiccharacter of the given method and universal character of the metaphor.It is stressed, that the study of the semantic method of the terminologicnomination in anatomical terminology contributes to the systematizationand regulation of the terms.
Keywords: terminologic nomination; terminoformation; semantic derivation; metaphor; motivization.